Synthesis and Properties of the Octaboron Cluster Series hypercloso‐B8Cl8, the Radical Anion hypercloso‐[B8Cl8].− and the Dianion closo‐[B8Cl8]2−. Issue 48 (18th November 2021) - Einholz, Wolfgang; Hofmann, Matthias; Schäfer, Ronald; Wieloch, Christoph; Keller, Willi; Ströbele, Markus; Meyer, Hans‐Jürgen
Abstract: The synthesis, spectroscopic data, redox properties of B8 Cl8, [B8 Cl8 ] .−, and [B8 Cl8 ] 2−, and the single‐crystal X‐ray structure analysis of [Ph4 P] + 2 [B8 Cl8 ] 2−  ⋅ CH3 CN are described. Temperature‐dependent 11 B NMR measurements and theoretical studies (DFT) concerning the fluxional behavior of [B8 Cl8 ] 2− will be discussed. – B8 Cl8 reacts with reductants like iodide to the intense purple colored radical anion [B8 Cl8 ] .− which is formed as well from B8 Cl8 by traces of water. The colorless dianion closo‐ [B8 Cl8 ] 2− is obtained by the reaction of B8 Cl8 or [B8 Cl8 ] .− with iodide. The single‐crystal X‐ray structure analysis of [Ph4 P] + 2 [B8 Cl8 ] 2− confirms the dodecahedral D 2d structure of [B8 Cl8 ] 2− . The 11 B NMR spectra of [B8 Cl8 ] 2− solutions show only one broad signal even at low temperatures due to the fast fluctuation of the [B8 Cl8 ] 2− polyhedron. The energy of the C 2v structure isomer of [B8 Cl8 ] 2− was calculated by DFT methods to be only 0.6 kcal/mol higher in energy than the D 2d form, and the activation barrier for the D 2d to C 2v transformation is predicted to be about 0.9 kcal/mol. Abstract : Little is known about the chemistry of the boron subhalide clusters B n Cl n ( n =4, 8–12). Here we describe some chemical properties of hypercloso ‐B8 Cl8, a prominent member of this series. The reduction of it leads to the radical anion hypercloso ‐B8 Cl8 − which can be further reduced to closo‐ [B8 Cl8 ] 2− . This polyhedron shows a remarkable fluxional mobility in solution.